A Narrative Review of the Confluence of Breast Cancer and Low-wage Employment and Its Impact on Receipt of Guideline-recommended Treatment. Issue 5 (September 2013) - Vanderpool, Robin C.; Swanberg, Jennifer E.; Chambers, Mara D.
Breast cancer is the leading cause of cancer among women in the United States, costing the healthcare system, employers, and society billions of dollars each year. Despite improvements in screening and treatment, significant breast cancer treatment and survivorship disparities exist among various groups of women. One variable that has not been explored extensively as a possible contributor to breast cancer treatment disparities is employment. This is concerning, given the changing economic and employment trends in the United States favoring low-wage employment. Currently, one-quarter to one-third of all US workers are considered to be working poor, and women are disproportionally represented in this group. Characteristics of low-wage work—limited paid time off, minimal health benefits, schedule inflexibility, and economic insecurity—may become even more significant in the event of a breast cancer diagnosis. To date, there has been limited research into how job conditions inherent to low-wage work may influence working poor survivors' receipt of guideline-recommended breast cancer treatment. Therefore, the purpose of this narrative review was to critically examine the current literature to further our understanding of how employment context may impact treatment decisions and adherence—and therefore receipt of guideline-recommended care—among newly diagnosed, working poor breast cancer survivors. After under-taking a comprehensive review, we failed to identify any published literature that explicitly addressed low-wage employment and receipt of guideline-recommended breast cancer treatment. Four articles reported circumstances where women delayed, missed, or quit treatments due to work interference, or alternatively, developed strategies that allowed them to continue to work and obtain their breast cancer treatment concurrent with medical and economic challenges. An additional five articles, while focused on other cancer and employment outcomes, described the need for increased patient-provider communication about the influence of work on treatment decisions and the development of alternative treatment plans. Due to the paucity of research in this area, future policy, practice, and research efforts should focus on the employment context of working poor breast cancer survivors as a potential contributor to cancer disparities. Engagement of women, employers, oncology providers, healthcare systems, and interdisciplinary researchers is warranted to improve cancer outcomes among this disparate population of working women.